Reliability, Validity, and Factor Structure of Pittsburgh Sleep Quality Index in Community-Based Centenarians - Zhang, Chi; Zhang, Hao; Zhao, Minghao; Li, Zhongquan; Cook, Chad E.; Buysse, Daniel J.; Zhao, Yali; Yao, Yao (Frontiers in Psychiatry, 2020)
Background: The Pittsburgh Sleep Quality Index (PSQI) is a widely used self-report questionnaire that measures general sleep quality in the elderly. However, its psychometric properties have yet to be thoroughly examined in longveous persons. Objectives: This study aimed to explore the reliability, validity and factor structure of the Chinese-language version of the PSQI in community-dwelling centenarians. Methods: A total of 958 centenarians (mean age = 102.8 years; 81.8% females) recruited from 18 regions in Hainan, China, completed the PSQI scale. Cronbach’s alpha coefficient was used to measure the internal consistency. Correlations between the global PSQI score and physical function, depression symptoms, self-reported health status and subjective well-being were used to assess divergent validity. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed to explore the validity and factor structure of the PSQI in this sample. Results: The Cronbach’s α coefficient of the PSQI was 0.68, and it increased to 0.78 after two components (medication use and daytime dysfunction) were removed. The Spearman correlation coefficients of the PSQI score with each component were statistically significant (P<0.01). EFA yielded a two-factor structure model of the original PSQI-7 and a one-factor structure model of the simplified PSQI-5. The one-factor model with 5 components (2/df =1.59, CFI=0.99, RMSEA=0.03) fit the data well and had good invariance across demographic characteristics in this sample. Conclusions: The original PSQI showed acceptable applicability in Chinese community-dwelling centenarians, and its psychometric characteristics moderately improved after sleeping medication and daytime dysfunction were removed. Further validation studies on PSQI are needed among centenarians from varied backgrounds.